Cortical Auditory Evoked Potential (CAEP) and the chirp Auditory Steady State Response (ASSR) in predicting behavioural hearing thresholds in adults with sensorineural hearing loss - Biagio, Leigh (University of Pretoria, 2020)
Dissertation (MA (Audiology))--University of Pretoria, 2019.